(NwSPYHIWA@]IE ZWEZDY I RODSTWENNYE OB_EKTY (B:s (NtRUDY SIMPOZIUMA(B, (Nb@RAKAN(B, 16-19 (NOKTQBRQ (B1984 (NG(B. /s - d; (Nb@RAKANSKAQ ASTROFIZI^ESKAQ OBSERWATORIQ an aRMQNSKOJ ssrs; (NsIMPOZIUM (B"(NwSPYHIWA@]IE ZWEZDY I RODSTWENNYE OB_EKTY(B"s (16-19 (NOKTQBRQ (B1984 :s (Nb@RAKAN(B)s ((NeREWAN (B:s (NiZD(B-(NWO an aRMssr(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE DOKL(B.s
(NzAGL(B. (NNA DOP(B.(NTIT(B.(NL(B.: Flare stars and related objects.s
(N~ASTX TEKSTA(B: (NANGL(B. (NrEZ(B. (NDOKL(B.: (NRUS(B., (NANGL(B.s
(NzAGL(B. (NTAKVE(B: (NARM(B.s
(Nw NADZAG(B.: (Nan aRMssr(B, (Nb@RAKAN(B. (NASTROFIZ(B. (NOBSERWATORIQs
Keywords: (NzWEZDYs -- (NwSPY[KIs